Refractory Plasmonics with Titanium Nitride: Broadband Metamaterial Absorber. (18th October 2014) - Li, Wei; Guler, Urcan; Kinsey, Nathaniel; Naik, Gururaj V.; Boltasseva, Alexandra; Guan, Jianguo; Shalaev, Vladimir M.; Kildishev, Alexander V.
<x xml:space="preserve">Abstract</x> A high‐temperature stable broadband plasmonic absorber is designed, fabricated, and optically characterized. A broadband absorber with an average high absorption of 95% and a total thickness of 240 nm is fabricated, using a refractory plasmonic material, titanium nitride. This absorber integrates both the plasmonic resonances and the dielectric‐like loss. It opens a path for the interesting applications such as solar thermophotovoltaics and optical circuits. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>